Energy-resolved mass spectrometry to investigate nucleobase triplexes – a study applied to triplex-forming artificial nucleobases. (8th April 2022) - Filho, Mauro Safir; Massi, Lionel; Millet, Antoine; Michel, Dylan; Moussa, Wafa; Ronco, Cyril; Benhida, Rachid
Abstract : This paper discloses the use of an energy-resolved mass spectrometric-based approach to assess the stabilities of base triplexes encompassing artificial nucleobases by using variable energy collision-induced dissociation. Abstract : The development and application of nucleobase triplex strategy has gained increasing attention. In this work, we disclose the pioneer use of energy resolved mass spectrometry to investigate A–U and G–C base triplexes with triplex-forming artificial nucleobases. This approach allows us to gain insight into the so-called bond dissociation energetics (BDE). The analysis of two families of nucleobase model frameworks, S (phenylthiazole bisamide) and HB (benzoxazole urea), bearing various substituents has enabled us to probe triplex formation as well as the structure–triplex stabilisation relationship. Moreover, the consistent fragmentation patterns of the triplexes support that CID can be a valuable method to uncover high performance triplex-forming artificial nucleobases.